Carnitine Level Changes with the Ketogenic Diet - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The effects of the ketogenic diet (KD) on carnitine levels were determined in 38 consecutive patients with epilepsy treated at Rush-Presbyterian-St Luke's Medical Center, Chicago, IL Carnitine levels were determined at 0, 1, 6, 12, and 24 months of diet treatment.